Education 3590. Moral education. No. 16. Interview with Dr. Glen Sheppard. - Magsino, Romulo F. (Teacher)
Dr. Romulo Magsino interviews Dr. Glen Sheppard on the psychoanalytic theory of moral development. An ETV production.